The Effect of Partial Defoliation on Growth Characteristics of Vitis vinifera L. cv. Cabernet Sauvignon II Reproductive Growth - Hunter, J.J.; Visser, J.H. (South African Journal of Enology and Viticulture, 2017)
The effect of partial defoliation over the whole canopy on the reproductive growth of Vitis vinifera L. cv. Cabernet Sauvignon was investigated. The 33% defoliation treatment prior to pea size and the 66% defoliation treatment prior to veraison adversely affected fresh mass per berry and yield at harvest. The 33% defoliation treatment from veraison increased fresh berry mass. Partial defoliation had no effect on berry water content. Dry matter started to accumulate rapidly only from after pea size stage. The fresh berry mass:cane mass ratio increased with partial defoliation from veraison. Leaf area/g fresh mass results indicated that control vines carried excess foliage which prevented maximum photosynthetic activity. Partial defoliation of the canopy improved budding percentage, generally increasing with increasing defoliation, whereas bud fertility was improved only by 33% defoliation. In general, leaf removal from bud break and berry set was more effective in improving budding, whereas bud fertility was favoured by partial defoliation from bud break.